THE MODEL OF EMPLOYEE’S PERFORMANCE OF ISLAMIC EDUCATION AGENCIES IN BANDUNG - Komar Priatna, Deden (Dinasti Publisher, 2021)
The purpose of this study was to know and analyze the Influence of leadership, organizational culture, and interpersonal communication toward work motivation and it’s implication to employee performance. The method used in this research were descriptive survey method and explanatory survey. The population in this study amounted to 254 employees of IEA (Islamic Education Agency in Bandung), with a sample size of 205 respondents. Analysis technique and hypothesis testing using Structural Equation Modeling (SEM) with LISREL 8.70 program. The result of research found that both partially and simultaneously leadership, organizational culture and interpersonal communication had positive and significant influence toward work motivation. Then also toward employee performance both partially and simultaneously leadership, organizational culture, interpersonal communication and work motivation had positive influence and significant. While, contribution percentage of leadership, organizational culture, interpersonal communication toward work motivation is 72% and contribution percentage of leadership, organizational culture, interpersonal communication, and work motivation simultaneous toward employee performance is 85%. The implication on this research is that the employee performance especially on the quantity will be able to be improved if IEA able to increase work motivation especially to the needs’ motivation, work motivation will increase if IEA is able to increase the leadership , especially in attitude dimension towards human, and increase the organizational culture especially to the internal integration, and supported by the improvement of interpersonal communication, mainly in social relationship. Furthermore, work motivation only have role for leadership and interpersonal communication variable toward employee performance, while for organizational culture variable, work motivation don’t have role to escalate employee performance, so in this model work motivation only as partial mediating.